Augmenting students’ learning for employability through post-practicum educational processes : final report. - Billett, Stephen; Cain, Melissa; Hai Le, Anh (Australia. Dept of Education and Training (DET), 2019)
Expectations are growing among governments, employers, parents and higher education students that university studies should lead to employable outcomes. That employability includes graduates having adequate occupational capacities to (i) commence employment upon graduation, (ii) successfully transition from higher education into work, (iii) practise the particular occupations for which they have prepared, and (iv) accommodate the needs of their workplaces. As a consequence, much attention is being given to the provision of work experiences to assist these outcomes. Going beyond those longstanding provisions, in education programs such as health care and education, that have included practicum or other kinds of workplace experiences, the provision of workplace experiences is becoming common across higher education programs. To optimise students’ ability to achieve these employability goals, it is insufficient merely to provide them with workplace experiences. These experiences need to be planned, enacted and otherwise integrated into the overall higher education experience and provision, and augmented by specific educational interventions. Earlier research indicates that certain educational processes and actions are needed before, during and after practical experiences to optimise learning. Particular kinds of educational practices associated with specific goals have been identified. [Publisher summary, ed]